Generation of Composite Plants in Medicago truncatula used for Nodulation Assays - Deng, Ying (MyJove Corporation, 2011)
Similar to Agrobacterium tumerfaciens, Agrobacterium rhizogenes can transfer foreign DNAs into plant cells based on the autonomous root-inducing (Ri) plasmid. A. rhizogenes can cause hairy root formation on plant tissues and form composite plants after transformation. On these composite plants, some of the regenerated roots are transgenic, carrying the wild type T-DNA and the engineered binary vector; while the shoots are still non-transgenic, serving to provide energy and growth support. These hairy root composite plants will not produce transgenic seeds, but there are a number of important features that make these composite plants very useful in plant research. First, with a broad host range,A. rhizogenes can transform many plant species, especially dicots, allowing genetic engineering in a variety of species. Second, A. rhizogenes infect tissues and explants directly; no tissue cultures prior to transformation is necessary to obtain composite plants, making them ideal for transforming recalcitrant plant species. Moreover, transgenic root tissues can be generated in a matter of weeks. For Medicago truncatula, we can obtain transgenic roots in as short as three weeks, faster than normal floral dip Arabidopsis transformation. Overall, the hairy root composite plant technology is a versatile and useful tool to study gene functions and root related-phenotypes. Here we demonstrate how hairy root composite plants can be used to study plant-rhizobium interactions and nodulation in the difficult-to-transform species M. truncatula.